Researchers Apply Lesson Study: A Cycle of Lesson Planning, Implementation, and Revision. Issue 2 (17th May 2016) - Regan, Kelley S.; Evmenova, Anya S.; Kurz, Leigh Ann; Hughes, Melissa D.; Sacco, Donna; Ahn, Soo Y.; MacVittie, Nichole; Good, Kevin; Boykin, Andrea; Schwartzer, Jessica; Chirinos, David S.
Abstract : Scripted lesson plans and/or professional development alone may not be sufficient to encourage teachers to reflect on the quality of their teaching and improve their teaching. One learning tool that teachers may use to improve their teaching is Lesson Study (LS). LS is a collaborative process involving educators, based on concepts of iteration and revision, to improve instruction. The initial use of an adapted version of LS referred to as a microteaching lesson study (MLS) is described in this article. Our purpose is to illustrate the process of MLS used by a group of researchers when developing lesson plans for teaching students with learning disabilities. We describe MLS, and then (1) share an application of MLS used by a research team in developing a writing intervention, and (2) discuss how the MLS format was mirrored with K‐12 teachers during professional development training.